COVID-19 response in Colombia: Hits and misses. Issue 2 (June 2022) - Prada, Sergio I.; Garcia-Garcia, Maria Paula; Guzman, Javier
Highlights: Colombia's response to the pandemic combines hits and misses. The country organized an early and robust response to the pandemic. Colombia shows signs of economic recovery, with real GDP growing by 6.1%. Colombia designed a risk-based, equitable, and inclusive vaccination strategy. Colombia has secured 99.7 million vaccines. To February 2022, only 11% of the total vaccines secured are still remaining to arrive. As of February 2022, Colombia's full vaccination rate is 80.47%, with 65.1% fully vaccinated and 19.9% with a complete scheme with booster dose. Abstract: Introduction: Colombia has been hit particularly hard by the COVID-19 pandemic, being ranked 22nd among 187 countries in deaths per 100, 000 people by February 2022. The country has also experienced the worst economic recession in its history, with real GDP contracting 7% in 2020. This paper describes Colombia's pre-pandemic context and the overall effect of the pandemic on health and economic indicators and examines the government's response to COVID-19. Methods: Descriptive chronologic policy analysis on the COVID-19 pandemic in Colombia and the measures and interventions implemented, using publicly available secondary data from Colombia's official agencies and international sources published from March 2020 to February 2022. Results: The Colombian healthcare system increased its capacity in terms of infrastructure and human resources (from 8.6 ICU beds per 100, 000 pre-pandemic to 21.9 in 2020, from 1.7 to 1.3 per 1000 doctors and nurses, respectively in 2019 to 1.8 and 1.5 per 1000 in 2020). The government commenced the National Vaccination Strategy on February 17, 2021, despite a slow start it managed to fully vaccinate 65.1% of its population, including Venezuelan immigrants, by February 2022. Conclusions: Colombia's response to the pandemic combines hits and misses. The country organized an early and robust response; increased its healthcare system capacity; designed a risk-based, equitable, and inclusive national vaccination strategy; and introduced a flexible and responsive vaccine rollout. However, the government chose the wrong timing for reform, implemented a long and unpredictable lockdown, was late to procure COVID-19 vaccines and has not appropriately tackled vaccine hesitancy. Public interest summary: Colombia has been hit particularly hard by the COVID-19 pandemic, with over 138, 000 COVID-19 deaths and over 6 million cases by the end of February 2022. According to number of deaths per 100, 000 people, Colombia ranks 22nd in the world, among 187 countries. The country has also experienced the worst economic recession in its history. The Colombian healthcare system has been able to cope with a high number of COVID-19 cases without collapsing, but some public health indicators deteriorated. Colombia's response to the pandemic combines hits and misses. The country organized an early and robust response; increased its healthcare system capacity; designed a risk-based, equitable, and inclusive national vaccination strategy; and introduced a flexible and responsive vaccine rollout. As of February 2022, Colombia has fully vaccinated 65.1% of its population. However, the government chose the wrong timing for a tax reform, implemented a long and unpredictable lockdown, was late to procure COVID-19 vaccines and has not appropriately tackled vaccine hesitancy, which certainly contributed to its undesirable position in the mortality world raking.